INTERSECTIONALITY AND OPPRESSION IN R. F. KUANG’S THE POPPY WAR NOVEL - Jannah, Sifani Syarifatul; Istiadah, Istiadah; Jaafar, Noornajihan (Department of English Literature, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This research presents a discussion of the main female character who experienced oppression in the novel The Poppy War by R. F. Kuang. The first part of the analysis describes the forms of oppression experienced by Rin in the novel based on the intersectional perspective. The second part analyses how Rin responded to the oppression that is caused by intersectional identity. This research employed feminist literary criticism as a literary approach. This study focused on oppression that is caused by intersectional identity that occurred to the main female character in The Poppy War novel. The results of this study showed that the types of oppression Rin experienced include marginalization, powerlessness, cultural imperialism, and violence that intersect with gender, race, and class. Rin was marginalized by her foster parents and peers who perceived her as unworthy. They limited her opportunities due to her gender and lower socioeconomic status. She faced powerlessness as her foster parents treated her as a shop girl and forced her to marry an old man due to her status as an orphan girl. She experienced cultural imperialism when she was forced to become a bride at a young age as her foster parents believed in the village culture. The last form of oppression was violence. In this case, she was mocked because of her skin colour, underestimated because of her gender, and kicked off because she originated from a lower-class society. Finally, the study showed that Rin’s response to oppression that is caused by intersectional identity was in the forms of negotiation and self-protection. These responses were carried out to escape from forced marriage, negotiate with her parents, and have more training to revenge the peers in The Poppy War.